Biomaterial surface patterning of self-assembled monolayers for controlling neuronal cell behaviour. (6th February 2009) - Murugan, Ramalingam; Molnar, Peter; Rao, Koritala Panduranga; Hickman, James J.
Control of the position, growth and subsequent function of living cells is a fundamental problem in cellular engineering. The development of a generation of 'smart' biomaterial requires strict control over the material's surface properties, because the initial response of the cultured cells mainly depends on the material's surface characteristics. Since most of the cells in the body are arranged in distinct patterns during development, it would be beneficial if one create patterned environments in vitro for regulating cell behaviour. Accordingly, we provide design strategies and methodologies developed for nano- and micro-scale surface patterning and the subsequent control of cellular responses.